Using wearable devices to generate real-world, individual-level data in rural, low-resource contexts in Burkina Faso, Africa: A case study - Huhn, Sophie; Matzke, Ina; Koch, Mara; Gunga, Hanns-Christian; Maggioni, Martina Anna; Sié, Ali; Boudo, Valentin; Ouedraogo, Windpanga Aristide; Compaoré, Guillaume; Bunker, Aditi; Sauerborn, Rainer; Bärnighausen, Till; et al. (Frontiers in Public Health, 2022)
Wearable devices may generate needed data for global health research for low- and middle-income-countries (LMICs). However, wearable studies in low-resource contexts are scarce. This case study aims to investigate the use of consumer-grade wearables to generate individual-level data in vulnerable populations in LMICs, focusing on the acceptability (quality of the devices being accepted or even liked) and feasibility (the state of being workable, realizable and practical) of wearable devices in rural Burkina Faso. We conducted a case study in Nouna, Burkina Faso utilizing a mixed-methods approach within the Health and Demographic Surveillance System (HDSS); data were collected over a period of 9-weeks. Every four days, a trained field worker conducted an acceptability questionnaire with the participants, which included questions on acceptance towards the wearables and their reliability. Descriptive and qualitative thematic analysis were used to analyze responses of study participants and field workers. In total, 148 study participants were included (excluding field workers). On average, participants slept seven hours (SD 3.2h) and walked 8000 steps per day (SD 5573.6 steps). Participant’s acceptability ranged from 94-100% throughout the questionnaire. In 95% of the cases (n=797 responses), participants reported no challenges with the wearable. Most study participants were not affected by the wearable in their daily activities (n=698 responses, 83%) and even enjoyed wearing them (n=91 responses, 19%). Some were concerned about damage to the wearables (n=40 responses, 5%). Total data coverage (i.e., the proportion of the whole 3-week study duration covered by data) was 43% for accelerometer (activity), 3% for heart rate, and 4% for body shell temperature. Technical issues like faulty synchronization (n=6, 1%) were reported. Acceptability as well as data completeness were comparable across sex, age, and study arms. This is the first study in rural Burkina Faso to investigate the implementation of wearables to generate objective data sets in rural communities. Wearable devices were well-accepted and were able to produce continuous measurements, highlighting the potential for wearables to generate large datasets in LMICs. Challenges constituted data missingness mainly of technical nature. More research is needed to understand the relationship between activity, vital patterns and health outcomes.